Raptor resource use in agroecosystems: cover crops and definitions of availability matter - Megan E. Zagorski (Resilience Alliance, 2021)
The populations of many species of raptors that forage in agroecosystems have declined as agriculture has intensified. Cover crops are a recent trend in areas of intensive row-crop agriculture in the Midwestern United States that could positively affect raptors by increasing the abundance and distribution of raptor prey. We assessed the habitat use of two raptors, American Kestrel (Falco sparverius) and Red-tailed Hawk (Buteo jamaicensis), and tested for use of areas near cover-cropped fields. We conducted 1184 km of roadside transects in 2018 and 2019 in west-central Indiana and recorded 191 detections of our focal species. We constructed resource selection functions within a use-availability design to evaluate raptor habitat use with a series of weighted logistic regression models. For each species, we fitted models at two scales (transect and landscape) and with two definitions of available points (completely random and random subject to perch constraints). American Kestrels were strongly associated with cover-cropped agricultural fields. Red-tailed Hawks were strongly associated with woodlots. Scale did not greatly affect the inclusion of habitat variables into top models for either species. Random models identified potential perch sites, whereas constrained random models identified more subtle habitat preferences not included in the random models. For American Kestrels, constrained models revealed reduced use of woodland perches and increased use of perches near cover-cropped and conventional agricultural fields. For Red-tailed Hawks, constrained models revealed habitat associations, particularly reduced use of utility lines and human development, that were absent or de-emphasized in random models. Modeling resource selection with constrained random availability will work best for well-studied species with discrete, easily mapped habitat features. If damage to commodity crops by rodents in cover-cropped fields is a concern, raptor management should focus on kestrels and could include erection of artificial perches, nest boxes, and enhancement of permanent herbaceous habitats for hunting.